The characteristics of the functioning of people with anorexia nervosa in the context of social change = Charakterystyka funkcjonowania osób z rozpoznaniem Anorexia Nervosa w kontekście zmiany społecznej - Boruc, Dagmara Maria; Pietrowska, Izabela (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this paper is to present selected aspects of eating disorders and their determinants in the context of social change. At the same time, an attempt is made to identify e?ective forms of complex and multifaceted interventions in the course of eating disorders. The most important aspects are presented in relation to the diagnosis and treatment of individuals with diagnosed with Anorexia Nervosa. A detailed review of Polish and foreign literature was therefore made. The latest analyses of this phenomenon have a noticeable impact on the perception and understanding of eating disorders.
Keywords: social change; Anorexia Nervosa; diagnosis; eating disorders; zmiana społeczna; diagnoza; zaburzenia odżywiania